TRAINING AND MENTORING GRADUATE TEACHING ASSISTANTS: A REVIEW OF THE LITERATURE - Eller, Ryan (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
Graduate Teaching Assistants (GTAs and TAs), at most four-year universities in the United States, are both employees and students of their universities, but also make up the important next wave of teaching professionals in the higher education system. Graduate TAs gain valuable experience from being in the classroom as students of their respective programs, but arguably even more so through learning how to design curriculum, teaching undergraduate students, grading using constructive feedback, and in many cases, how to research a populous that they interact (the students that they teach) with on a day-to-day basis. As such, it is imperative that these future higher education faculty and professionals be supported in their development through routine mentoring and training practices. During this formative developmental period, it can be argued that building a strong and effective mentoring program should be guided using human resource theory principles. These principles include open communication and feedback, treating these future faculty members as an important and immediate investment of the academy, which ultimately leads to a more empowered and engaged workforce. Engaged GTAs ultimately will serve as not only better teachers for their undergraduate students, but will also provide a clearer articulation of what a successful graduate student is to the students that they teach.